Pengaruh Tugas Akhir Terhadap Kejadian Premenstrual Syndrome (PMS) Dan Perilaku Saat PMS - Tatik Trisnowati; Sri Lestari; Marni Marni (Jurnal Kesehatan Indonesia, 2020)
Final task is one of the requirements for student graduation. Provisions regarding the final project are regulated by each faculty, following the university's standards. Final task for diploma III students is in the form of paper or final task. Final task at Nursing Academy, Insann Husada Surakarta is in the form of case study. In general, students who are writing their final assignments often experience difficulties. Difficulties faced are very diverse, ranging from lack of understanding the phenomenon being studied, lack of mastering the theory, limited references and so on. Women who are more prone to suffer from premenstrual syndrome are women who are more sensitive to hormonal changes in the menstrual cycle and to psychological factors. Purpose. This study aims to determine how the effect of the Final task on the incidence of Premenstrual Syndrome (PMS) and Behavior when PMS on Students.Methods This research is a descriptive analytic study with cross sectional approach. By using purposive sampling technique, a sample of 30 female students was obtained. Data collection tools and methods used were questionnaires and processed with the Pearson correlation test.Result. The results of research that have been done obtained the incidence of PMS in respondents in the last 3 months by 50%. The average respondent has a heavy behavior when facing PMS that is equal to 63.3%. The results of the study show that between the final project with the occurrence of PMS has a significance value of 0.041 (p <0.05) which means there is an influence between the final project with the PMS event with the degree of relationship based on the Pearson Correlation value of 0.429, which means that the relationship is weak between the final project and the occurrence of PMS. While the effect of the final project with PMS behavior shows a significance value of 0.042 (p <0.05) which means there is a relationship between the final project with the occurrence of PMS with the degree of relationship based on the Pearson Correlation value of 0.275, which means a weak relationship between the final task with PMS behavior. Conclusion. It was concluded that there was an effect of the final assignment on the incidence of PMS and PMS Behavior in female students at the Surakarta Husada Insan Nursing Academy.